Analysis of Existing Slope Reinforcement Design on Clay Shale Soil and Its Alternative Modifications: A Case Study of the Awunio – Lapuko Road Section Sta 4+955 – 5+015 in the Southeast Sulawesi Province - Azhari, A.; Khoiri, Mohamad; Siagian, Freddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
A landslide occurred in the Awunio – Lapuko road section from STA 4+955 to STA 5+015, causing the road shoulder to collapse. It is estimated that the cause of this is the entry of water into the soil, affecting the properties of clay shale. An analysis of the existing slope stability and its planning needs to be done. Water management planning and alternative reinforcement are necessary if the stability does not meet the requirements. The slope stability analysis is conducted on the existing slope and the existing design using manual calculation methods and the GEO5 software. The stability aspects considered include overturning stability, sliding stability, bearing capacity, and overall stability. The analysis of the existing slope stability shows safety from landslide incidents. However, this contradicts the field observations, so a crack soil approach is used to understand the landslide conditions in the field, resulting in a safety factor (SF) of 0.95. The existing design, which includes a retaining wall with bored piles, yields a slope stability with an SF of 7.87. Water management system planning indicates that the drainage channel capacity can still accommodate the water flow resulting from rainfall. The construction of subdrains increases the SF on the slope to 1.38 but requires additional reinforcement. The retaining wall design with bored pile results in a slope stability 2.11. Meanwhile, the alternative of subdrains with additional geotextile reinforcement yields a slope stability of 1.96. The alternative geotextile design achieves slope stability with an SF of 1.77, ensuring safety and meeting stability requirements.